Anti-NMDA-Receptor Encephalitis in a Patient with Ovarian Teratoma, Harboring Brain Histology of Varying Developmental Stages and Regions with Chronic Inflammation. (28th October 2021) - Fatemi, S; Qu, E; Fullmer, J
Abstract: Introduction/Objective: Anti-NMDA-receptor encephalitis is a subacute, autoimmune disorder thought to be caused by autoantibodies directed against the N-methyl-D-aspartate (NMDA) receptor. Clinical symptoms of anti-NMDAR encephalitis may mimic schizophrenia and psychotic spectrum disorders or substance-induced psychosis. Although initially described in association with ovarian teratomas in women, anti-NMDAR encephalitis has been reported in individuals without paraneoplastic association, as well as in males. Herein, we report a case of a 29-year-old woman with suicidal ideation and other neuropsychiatric manifestations who was found to have a right ovarian cystic mass by imaging study. Microscopically, the resected ovarian mass is composed of mature skin, fat, cartilage and neural tissues. Nerve, ganglions and multiple brain tissues are present. Cerebellum including external granular cell layer (normally only seen in infants), cerebrum-like, choroid plexus and other neural elements are present. There is peripheral lymphoplasmacytic infiltrates around and within the neuroglial matrix. Cerebral spinal fluid was concurrently tested positive for Anti-NMDAR. The combined clinical, histological, and laboratory findings confirmed the above diagnosis. Although Anti-NMDAR encephalitis is a familiar entity to many clinical psychiatrist and neurologists, it is less commonly reported in the pathology literature. Its resultant relationship to cystic teratoma warrants awareness of this condition by pathologists. Methods/Case Report: Case Report Results (if a Case Study enter NA): NA Conclusion: Anti-NMDA-receptor encephalitis is related to cystic teratoma, therefore pathologists need to be aware of this condition.